Toward a phenomenology of addiction : embodiment, technology, transcendence - Schalow, Frank (Springer, 2020)
This book addresses an epidemic that has developed on a global scale, and, which under the heading of "addiction," presents a new narrative about the travails of the human predicament. The book introduces phenomenological motifs, such as desire, embodiment, and temporality, to uncover the existential roots of addiction, and develops Martin Heidegger's insights into technology to uncover the challenge of becoming a self within the impulsiveness and depersonalization of our digital age. By charting a new path of philosophical inquiry, the book allows a pervasive, cultural phenomenon, ordinarily reserved to psychology, to speak as a referendum about the danger which technology poses to us on a daily basis. In this regard, addiction ceases to be merely a clinical malady, and instead becomes a "signpost" to exposing a hidden danger posed by the assimilation of our culture within a technological framework